Konsep Pembebanan Pembuktian Terbalik Dalam Perkara Pengakuan Ayah Biologis (Analisis Putusan Banding No.109/Pdt/2022/Pt Btn) - Anjasmara Arrizal Mahfud; Achmad Hasan Basri (SAKINAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the application of the reverse burden of proof in a civil case through the Decision of the Banten High Court Number 109/Pdt/2022/PT BTN. The case is noteworthy because the reverse burden of proof is generally applied in special criminal cases such as corruption or money laundering. In this case, however, the judges applied it in a tort case concerning the determination of a biological father, despite the general principle of civil evidence that “whoever asserts a claim must prove it.” This research uses a normative juridical method with conceptual, statutory, comparative, and case approaches. The analysis is based on primary and secondary legal materials to examine the normative framework and the value of substantive justice in the application of the reverse burden of proof. The results show that the judges in the Banten High Court decision adopted a more progressive approach in assessing evidence of a biological father–child relationship. From the perspective of positive law, the judges did not rigidly apply the burden of proof principle under Article 163 HIR or Article 1865 of the Indonesian Civil Code. Instead, they considered the evidentiary difficulties faced by the plaintiff and allowed the possibility of shifting the burden of proof to the defendant, consistent with the spirit of Constitutional Court Decision Number 46/PUU-VIII/2010. From the perspective of Islamic law, this reasoning is consistent with the principle of protecting lineage (ḥifẓ al-nasl) within the framework of maqāṣid al-sharīʿah. Scientific evidence such as DNA testing may be analogized to the concepts of qiyāfah and qarīnah in Islamic jurisprudence for establishing lineage. Thus, the reverse burden of proof in this case is better understood as a situational shifting of the burden of proof aimed at achieving substantive justice and protecting the rights of the child.